2012
DOI: 10.1111/j.1365-2044.2012.07193.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamics in women with untreated pre‐eclampsia*

Abstract: SummaryThis study aimed to compare the haemodynamics in healthy pregnant women with the haemodynamics in women with untreated pre-eclampsia, to determine the cardiovascular reason for hypertension in pre-eclampsia. 40 women with untreated pre-eclampsia, 40 matched healthy pregnant women and 20 non-pregnant women were studied using transthoracic echocardiography. Untreated pre-eclampsia demonstrated (mean (SD), healthy non-pregnant vs healthy pregnant vs untreated pre-eclampsia) increased cardiac output (3400 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 46 publications
6
67
1
5
Order By: Relevance
“…27,38,40,53,57 Interestingly E/e′ was shown to be significantly higher in an early-onset preeclampsia subgroup compared with a late-onset subgroup. 40 One study used a composite of diastolic indices to diagnose diastolic dysfunction and demonstrated diastolic dysfunction in 40% of pregnancies complicated by preeclampsia at term, compared with 14% of controls.…”
Section: Diastolic Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…27,38,40,53,57 Interestingly E/e′ was shown to be significantly higher in an early-onset preeclampsia subgroup compared with a late-onset subgroup. 40 One study used a composite of diastolic indices to diagnose diastolic dysfunction and demonstrated diastolic dysfunction in 40% of pregnancies complicated by preeclampsia at term, compared with 14% of controls.…”
Section: Diastolic Functionmentioning
confidence: 99%
“…The use of different calculations (based either on Doppler or volume calculation) is likely to contribute to the disparity for this parameter. There was similar variability with regard to LV ejection fraction, with the majority of studies showing no significant difference compared with normotensive pregnant women 30,38,52,56,57 and only 1 showing a decrease. 33 Myocardial performance index was reduced in a study of women with preeclampsia and fetal growth restriction in the third trimester.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Під час вагітності спостерігаються певні зміни розподілу рідини в організмі жінок, які в більшій мірі торкаються позаклітинного простору і обумов-люються забезпеченням потреб для росту і розвит-ку плода [6]. У нормі вміст рідини у вагітних жі-нок в середньому складає 65-70 % маси тіла, з яких 6-8 % приходиться на внутрішньосудинний сектор, 15 % -на інтерстиціальний і 40-50 % -на внутріш-ньоклітинний простір.…”
Section: обґрунтування дослідженняunclassified